The Effects of Teacher Motivation as Innovation in Teaching English - Akram, Muhammad; Rana, Muhammad Saleem (Journal of English Language and Literature (ISSN: 2368-2132), 2019)
Innovative teaching can inspire learning with interest. Teachers are supposed to be very innovative and agents of real change. A teacher’s teaching methodologies should be supple to assimilate new techniques springing up in the realm of teaching in general and in teaching English in particular. A teacher should revise his/her stratagem of delivering his approach to succumb students’ interest in each of the academic sessions. The present study explores how the teacher motivation can enhance the standards of language learning and how innovative effective their interactive approach could be if the theoretical methods of teaching are replaced by practical ones.